Method for improving humification of straw compost

By adding soluble lignin, oxidized metal cation and wetter to the straw compost, the problem of large gaseous loss, low retaining rate of dry substances and low salt acid content in straw compal of straw compal of straw. Acid content, extend the effect of high temperature period.

CN119350071APending Publication Date: 2025-01-24SHENYANG INST OF APPL ECOLOGY CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531078.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When dealing with straw compost, there are problems such as large loss of gaseous substances, low dry matter retention, low humic acid content, slow heating up and short high temperature period, which limits the process and quality of straw compost.

Method used

By adding soluble lignin (calcium lignosulfonate) to provide a core skeleton for humic acid formation, and by adding oxidizing metal cations (iron sulfate) for chemical oxidation, biological oxidation gaseous losses are reduced. At the same time, wetting agent ingredients (hydroxyethyl cellulose and betaine) are added to maintain moisture and promote cellulose dissolution, extending the high temperature period.

Benefits of technology

The retention rate of dry substances and rodentic acids that compost composting, extended the high temperature period, and improved the quality and efficiency of composting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350071A_ABST
    Figure CN119350071A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fermentation, in particular to a method for improving humification of straw compost. Mixing a ferric sulfate solution with the granular straws, and adsorbing to obtain adsorbed straws; mixing calcium lignosulphonate, hydroxyethyl cellulose, betaine and water to obtain turbid liquid; and mixing the adsorbed straws, the turbid liquid and the straws to be fermented, and carrying out aerobic fermentation. By adding the soluble lignin, a core framework is provided for formation of humic acid in the middle and later periods of compost, sites are provided for condensation of decomposed organic matters, and the condensation process of formation of the humic acid of the compost organic matters is facilitated; by adding oxidizing metal cations, the compost material is directly subjected to chemical oxidation, so that the gaseous loss of biological oxidation is reduced, and the retention rate of dry matters is increased; by adding the wetting agent, the moisture of the compost can be maintained, more straw cellulose and hemicellulose degradation products can be dissolved in water, the subsequent compost reaction process is facilitated, and the high-temperature period is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fermentation, in particular to a method for improving the humification of straw compost. Background Art

[0002] Composting is the process of converting biodegradable organic matter into stable humus through microbial decomposition and transformation under certain artificial conditions. Composting has the characteristics of large processing capacity, simple process and good economy, and is a widely used method of recycling organic waste. Crop straw, as the largest agricultural organic waste, is not only the main raw material of composting but also a commonly used compost conditioner. It plays an important role in regulating the moisture content, carbon-nitrogen ratio (C / N) and porosity of materials.

[0003] Although composting technology is relatively mature, there is still room for improvement when processing straw, especially composting raw materials mainly based on the straw of grain crops such as rice and corn. On the one hand, when straw is used as the main composting material, the gaseous matter loss of the material is large, and the dry matter retention rate is only about 40-50%; on the other hand, the humic acid content of the compost product is relatively low, only about 3%. Measured by the humic acid content, the quality of the compost product is not high; at the same time, when straw is used as the main material, the composting process heats up slowly and the high temperature period is short, which is the main technical problem limiting the progress of straw composting and the improvement of compost quality. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for improving the humification of straw compost. The method provided by the present invention not only provides a core skeleton for the formation of humic acid in the middle and late stages of composting, but also provides sites for the condensation of decomposed organic matter, which is beneficial to the condensation process of humic acid formation of compost organic matter; at the same time, by adding oxidizing metal cations (ferric sulfate), the compost material is directly chemically oxidized, the gaseous loss of biological oxidation is reduced, and the dry matter retention rate is improved; in addition, the technical method, by adding wetting agent components (hydroxyethyl cellulose and betaine), is not only beneficial to the retention of compost moisture, but also can make more straw cellulose and hemicellulose degradation products dissolve in water, which is beneficial to the subsequent composting reaction process and prolongs the high temperature period.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for improving the humification of straw compost, comprising the following steps:

[0007] 1) mixing and adsorbing the ferric sulfate solution and the granular straw to obtain adsorbed straw;

[0008] 2) mixing calcium lignin sulfonate, hydroxyethyl cellulose, betaine and water to obtain a suspension;

[0009] 3) mixing the adsorbed straw obtained in step 1), the suspension obtained in step 2) and the straw to be fermented, and performing aerobic fermentation;

[0010] There is no time sequence limitation for steps 1) and 2).

[0011] Preferably, the concentration of the ferric sulfate solution in step 1) is 100 g / L.

[0012] Preferably, the volume ratio of the ferric sulfate solution to the mass ratio of the granular straw is 100 mL: 70-80 g;

[0013] The particle size of the granular straw is 0.5-1 cm.

[0014] Preferably, in step 2), the mass ratio of calcium lignin sulfonate, hydroxyethyl cellulose, betaine and water is 80-94:23-25:23-25:500.

[0015] Preferably, in step 3), the mass ratio of the adsorbed straw, the volume of the suspension and the mass ratio of the straw to be fermented is 180-190 g:500 mL:3.1-3.3 kg.

[0016] Preferably, in step 3), the carbon-nitrogen ratio of the straw to be fermented is 30:1, and the moisture content is 60-62%.

[0017] Preferably, the conditions for aerobic fermentation in step 3) include: turning the compost twice a day.

[0018] Preferably, the granular straw includes rice straw and / or corn straw;

[0019] The straw to be fermented includes rice straw and / or corn straw.

[0020] Preferably, the rice straw has a moisture content of 10%, a cellulose content of 40.1%, and a lignin content of 6.3%, all of which are percentages by mass.

[0021] Preferably, the corn stalk has a moisture content of 11%, a cellulose content of 34.7%, and a lignin content of 5.3%, all of which are mass percentages.

[0022] Beneficial effects of the present invention:

[0023] The present invention adds humus-promoting strengthening substances in a proportion in a conventional aerobic composting process, and provides a core skeleton for the formation of humic acid through the added soluble lignin component, provides a site for the condensation of decomposed organic matter, is beneficial to the condensation process of humic acid formation of composted organic matter, and increases the humic acid content of the compost;

[0024] The iron sulfate adsorbed by the straw plays a role of direct oxidation and oxidation catalysis. Since the iron sulfate is adsorbed in the straw, it is slowly released during the composting process, avoiding the loss of iron sulfate when it comes into contact with water when it is directly added; the iron ions released during the composting process use the cellulose and hemicellulose structures in the straw to be destroyed through direct chemical oxidation, exposing the groups in the straw and increasing the possibility of further combination to form humic acid precursors; chemical oxidation partially replaces microbial respiratory oxidation, reduces the gaseous loss of microbial respiratory oxidation, and improves the dry matter retention rate; the acidity of iron sulfate can not only buffer the increase in pH of the composting material caused by the release of basic ions during the composting process, stabilize the living environment of microorganisms during the composting process, and promote the maintenance of the temperature of the compost; it can also form a small amount of iron hydroxide, which can adsorb small molecules decomposed in the composting material through the colloidal coagulation of iron hydroxide, which is conducive to the aggregation of humic substances;

[0025] The added hydroxyethyl cellulose and betaine mainly play the role of wetting, spreading and retaining moisture. They can not only more effectively create conditions suitable for composting microbial reactions and increase the composting reaction temperature more quickly, but also make more straw cellulose and hemicellulose degradation products dissolved in water, reduce gaseous losses, and facilitate the subsequent composting reaction process.

[0026] Iron is widely present in natural soil. The added iron sulfate is basically integrated after composting and has no environmental harm. The added hydroxyethyl cellulose and betaine are both biodegradable organic substances and do not pose any environmental risks. The added calcium lignin sulfonate is a sulfonate of lignin, which itself comes from plant fiber components and can serve as a core substance of humus. It also has a certain soil carbon fixation effect. It not only has no environmental harm but also promotes the adsorption of soil carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The temperature changes of the compost piles of conventional rice straw composting and the compost piles of the present technical solution;

[0028] Figure 2 Infrared image of the temperature of the rice straw compost pile in this technical solution;

[0029] Figure 3 The invention discloses an implementation process of film-covered aerobic composting fermentation using the technical solution. DETAILED DESCRIPTION

[0030] The present invention provides a method for improving the humification of straw compost, comprising the following steps:

[0031] 1) mixing and adsorbing the ferric sulfate solution and the granular straw to obtain adsorbed straw;

[0032] 2) mixing calcium lignin sulfonate, hydroxyethyl cellulose, betaine and water to obtain a suspension;

[0033] 3) mixing the adsorbed straw obtained in step 1), the suspension obtained in step 2) and the straw to be fermented, and performing aerobic fermentation;

[0034] There is no time sequence limitation for steps 1) and 2).

[0035] The present invention mixes and adsorbs ferric sulfate solution and granular straw to obtain adsorbed straw. In the present invention, the concentration of the ferric sulfate solution is preferably 0.1g / mL. In the present invention, the mass ratio of the volume of the ferric sulfate solution to the granular straw is preferably 100mL:70-80g; the particle size of the granular straw is preferably 0.5-1cm. In the present invention, the granular straw preferably includes rice straw and / or corn straw. In the present invention, the water content of the rice straw is preferably 10%, the cellulose content is preferably 40.1%, and the lignin content is preferably 6.3%, all of which are mass percentages. In the present invention, the water content of the corn straw is preferably 11%, the cellulose content is preferably 34.7%, and the lignin content is preferably 5.3%, all of which are mass percentages.

[0036] The present invention mixes calcium lignin sulfonate (potassium lignin xanthate can be used, but sodium lignin sulfonate should be avoided, mainly because sodium ions have a dispersing effect and will reduce the binding effect of generating humic acid small molecules), hydroxyethyl cellulose (hydroxymethyl cellulose can also be used), betaine (betaine is biodegradable and suitable under composting conditions. Although ionic surfactants can also be used instead, more foam is generated and the impact on the composting process is unknown) and water to obtain a suspension. In the present invention, the mass ratio of the calcium lignin sulfonate, hydroxyethyl cellulose, betaine and water is preferably 80-94:23-25:23-25:500.

[0037] The present invention mixes the obtained adsorption straw, the obtained suspension and the straw to be fermented for aerobic fermentation. In the present invention, the mass of the adsorption straw, the volume of the suspension and the mass ratio of the straw to be fermented are preferably 180-190g:500mL:3.1-3.3kg. In the present invention, the carbon-nitrogen ratio of the straw to be fermented is preferably 30:1, and the moisture content is preferably 60-62%. The present invention preferably uses urea to adjust the carbon-nitrogen ratio of the straw to be fermented. In the present invention, the straw to be fermented preferably includes rice straw and / or corn straw. In the present invention, the water content of the rice straw is preferably 10%, the cellulose content is preferably 40.1%, and the lignin content is preferably 6.3%, all of which are mass percentages. In the present invention, the water content of the corn straw is preferably 11%, the cellulose content is preferably 34.7%, and the lignin content is preferably 5.3%, all of which are mass percentages. In the present invention, the conditions for aerobic fermentation include oxygen supply to the pile body achieved by means of turning the pile, ventilation and aeration.

[0038] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0039] Unless otherwise specified, the experimental methods used in the following specific examples are all conventional methods.

[0040] In the following specific examples, the operations involved in the operation without specifying the conditions were all carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials used without specifying the manufacturer and specifications were all conventional products that can be obtained through commercial purchase.

[0041] Calcium lignin sulfonate, Tianjin Huasheng Chemical Reagent Co., Ltd., analytical grade; hydroxyethyl cellulose, Beijing Youtelang Trading Co., Ltd., food grade, purity 98%; betaine, Shengyuan Biotechnology Co., Ltd., purity 99%; ferrous sulfate, Sinopharm Chemical Reagent Co., Ltd., analytical grade.

[0042] Example 1

[0043] 3.3 kg of rice straw was used as compost material. The moisture content was 10% and the dry weight of the straw was about 3 kg. The cellulose content of the rice straw was about 40.1% and the lignin content was 6.3%, all of which were percentages by mass.

[0044] S1. Weigh 10 g of ferric sulfate, add 100 mL of water to dissolve, and take 80 g of rice straw with a particle size of 0.5-1 cm for adsorption to obtain straw adsorbing ferric sulfate;

[0045] S2, weigh 80g of calcium lignin sulfonate, 25g of hydroxyethyl cellulose and betaine, add 500mL of water and mix the above materials evenly to form a suspension;

[0046] S3, adding 21g of urea, adjusting the C / N ratio of the compost straw material to 30:1, adding 4.5kg of water, using the compost material with a moisture content of 60%, to obtain the adjusted straw compost material;

[0047] S4. Evenly mix the straw adsorbed with iron sulfate, the suspension and the adjusted straw compost material and put them into a plastic box with a volume of 108L (600*400*450mm) for composting. Perform aerobic fermentation by turning the compost twice a day with an interval of 12 hours.

[0048] Compared with the same materials, under the conditions of a carbon-nitrogen ratio of 30:1 and a moisture content of 60% for the composting materials, without adding the materials of the technical solution and using the conventional composting in the same turning method, the medium-high temperature period (>40°C) of the humus-enhanced composting using the technical solution can reach 9 days, which is significantly longer than the 2-3 days of conventional composting of the same materials ( Figure 1 , Figure 2 ), the maximum composting temperature is also higher than that of conventional composting; at the same time, after applying the technical solution, the temperature of rice straw composting rises more rapidly, and the high temperature range can be reached on the first day of composting ( Figure 2 ).

[0049] After 42 days of composting, the humic acid content of the technical solution was measured according to the GBT34766-2017 method to be 5.5%, and the dry matter retention rate was 71%.

[0050] Example 2

[0051] 3.1 kg of corn stalks were used as compost material. The moisture content was found to be 11% and the dry matter mass of the stalks was about 2.8 kg. The cellulose content of the corn stalks was about 34.7% and the lignin content was 5.3%, all of which were expressed in mass percentages.

[0052] S1. Weigh 10 g of ferric sulfate, add 100 mL of water to dissolve, and take 70 g of corn stalks with a particle size of 0.5-1 cm for adsorption to obtain stalks adsorbed with ferric sulfate;

[0053] S2, weigh 94g of calcium lignin sulfonate, 23g of hydroxyethyl cellulose and betaine, add 500mL of water to mix the above materials and stir evenly to form a suspension;

[0054] S3, adding 46g of urea, adjusting the C / N ratio of the compost straw material to 30:1, adding 4.5kg of water, using the compost material with a moisture content of 62%, to obtain the adjusted straw compost material;

[0055] S4. Evenly mix the straw adsorbed with iron sulfate, the suspension and the adjusted straw compost material and put them into a plastic box with a volume of 108L (600*400*450mm) for composting. Perform aerobic fermentation by turning the compost twice a day with an interval of 12 hours.

[0056] After 40 days of aerobic composting, the medium-high temperature period (>40°C) of the humus-enhanced composting using the technical solution was 8 days, which was longer than 4 days of conventional composting. At the end of composting, the mass fraction of humic acid in the technical solution measured by the GBT34766-2017 method was 7.3%, and the dry matter retention rate was 67%.

[0057] Example 3

[0058] Taking 100 kg of cow dung and 5.9 kg of corn stalks as materials, the test showed that the moisture content of the corn stalks was 9%, and the dry mass of the stalks was about 5.3 kg; the cellulose content of the corn stalks was about 34.1%, and the lignin content was 5.6%, all of which were mass percentages.

[0059] S1. Weigh 32 g of ferric sulfate, add 350 ml of water to dissolve, and take about 260 g of corn stalks with a particle size of 0.5-1 cm to obtain stalks adsorbed with ferric sulfate;

[0060] S2, weigh 180g of calcium lignin sulfonate, 45g of hydroxyethyl cellulose and betaine, add 1000mL of water to mix the above materials evenly to form a suspension;

[0061] S3, after the compost materials are mixed, the moisture content is adjusted to 61%, and the carbon-nitrogen ratio is 30:1, to obtain the adjusted cow dung straw compost material;

[0062] S4. Evenly mix the straw adsorbed with ferric sulfate, the suspension and the adjusted straw compost material to form a fermentation pile of 2 meters in length, 70 cm in width and 60 cm in height. Use static composting fermentation process, cover with a composting special film, and perform aerobic composting with a perforated ventilation pipe (ventilation interval is 15 minutes every 4 hours to maintain the oxygen content of the pile at 5%). The composting time is 45 days ( Figure 3 );

[0063] After 45 days of aerobic composting, the medium-high temperature period (>40°C) of the humus-enhanced composting using the technical solution was 6 days; at the end of composting, the humic acid mass fraction of the technical solution measured according to the GBT34766-2017 method was 6.9%, and the dry matter retention rate was 59.7%.

[0064] Comparative Example 1

[0065] 3.3 kg of rice straw was used as compost material. The moisture content was 10% and the dry weight of the straw was about 3 kg. The cellulose content of the rice straw was about 40.1%, and the lignin content was 6.3%, all of which were mass percentages. 21 g of urea was added to adjust the C / N of the compost straw material to 30:1. 4.5 kg of water was added, and the moisture content of the compost material was 61%. The adjusted straw compost material was put into a volume of 108 L (600*400*450 mm). No materials of the present technical solution were added, and aerobic composting was carried out. Aerobic ventilation was carried out by turning the pile twice a day with an interval of 12 hours. The time during the composting process when the pile temperature is greater than 40°C is 2-3 days ( Figure 1 ), after 42 days of composting, the mass fraction of humic acid in conventional compost was determined according to the GBT34766-2017 method and the dry matter retention rate was 2.9%.

[0066] Comparative Example 2

[0067] 3.1 kg corn stalks were used as compost materials, and the moisture content was 11% after testing, and the dry matter weight of the stalks was about 2.8 kg; the cellulose content of the corn stalks was about 34.7%, and the lignin content was 5.3%, all of which were mass percentages. 46 g of urea was added to adjust the C / N of the compost stalk material to 30:1, 4.5 kg of water was added, and the moisture content of the compost material was 61%, and the adjusted stalk compost material was obtained; a volume of 108 L (600*400*450 mm) was put in, and the material of the technical solution was not added, and aerobic composting was performed, and aerobic ventilation was performed by turning the compost twice a day at an interval of 12 hours.

[0068] After 40 days of aerobic composting, the medium-high temperature period (>40°C) of composting was 4 days; at the end of composting, the mass fraction of humic acid of the technical solution measured according to the GBT34766-2017 method was 4.2%, and the dry matter retention rate was 53%.

[0069] Comparative Example 3

[0070] Taking 100 kg of cow dung and 5.9 kg of corn stalks as materials, the test showed that the moisture content of the corn stalks was 9%, and the dry weight of the stalks was about 5.3 kg; the cellulose content of the corn stalks was about 34.1%, and the lignin content was 5.6%.

[0071] Without adding calcium lignin sulfonate, according to the technical solution, 45 g of hydroxyethyl cellulose and betaine were weighed, 1000 mL of water was added, and the above materials were mixed and stirred evenly to form a solution;

[0072] 35g MnO2 powder was used as an oxidant to replace the iron sulfate in the technical solution. After being uniformly mixed with the suspension, cow dung and corn stalks, a fermentation pile of 2 meters, 70cm wide and 60cm high was grown. The same static composting fermentation process as in the embodiment was adopted. After covering with a composting special film, aerobic composting was carried out with a perforated ventilation pipe (ventilation interval was 15 minutes every 4 hours to maintain the oxygen content of the pile at 5%). The composting time was 45 days ( Figure 3 ), the embodiment and the comparative example are directly separated by a plastic plate.

[0073] After 45 days of aerobic composting, MnO2 powder was used instead of ferric sulfate, and the medium-high temperature period (>40°C) of composting was 4 days; at the end of composting, the humic acid mass fraction of the technical solution measured according to the GBT34766-2017 method was 5.5%, and the dry matter retention rate was 33.4%.

[0074] Comparative Example 4

[0075] 3.0kg corn stalks were used as compost materials, and the moisture content was 10% after testing, and the dry matter weight of the stalks was about 2.7kg; the cellulose content of the corn stalks was about 34.7%, and the lignin content was 5.3%, all of which were mass percentages. 48g of urea was added, and the C / N of the compost stalk material was adjusted to 30:1. 4.6kg of water was added, and the moisture content of the compost material was 62%. The adjusted straw compost material was obtained, and similar material ratios were formed into 4 groups, and the volume was 108L (600*400*450mm) respectively. According to the addition method of iron sulfate in the technical solution, 5g, 10g, 20g and 40g of iron sulfate were added respectively for aerobic composting. The addition method of other materials was the same as the requirements of the technical solution, and aerobic composting was carried out, and aerobic ventilation was carried out by turning the pile twice a day with an interval of 12 hours.

[0076] After 40 days of aerobic composting, at the end of composting, the differences in duration of high temperature period, humic acid content, dry matter retention rate and germination index of compost materials in composting were mainly:

[0077] Table 1 Effect of different amounts of iron sulfate added on composting effect

[0078]

[0079] *It has not reached mature compost state. Mature compost requires germination index greater than or equal to 80%.

[0080] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for improving the humification of straw compost, characterized in that: The following steps are involved: 1) mixing and adsorbing the ferric sulfate solution and the granular straw to obtain adsorbed straw; 2) mixing calcium lignin sulfonate, hydroxyethyl cellulose, betaine and water to obtain a suspension; 3) mixing the adsorbed straw obtained in step 1), the suspension obtained in step 2) and the straw to be fermented, and performing aerobic fermentation; There is no time sequence limitation for steps 1) and 2).

2. The method according to claim 1, characterized in that The concentration of the ferric sulfate solution in step 1) is 100 g / L.

3. The method according to claim 1 or 2, characterized in that: The volume ratio of the ferric sulfate solution to the mass ratio of the granular straw is 100 mL: 70-80 g; The particle size of the granular straw is 0.5-1 cm.

4. The method according to claim 1, characterized in that: In the step 2), the mass ratio of calcium lignin sulfonate, hydroxyethyl cellulose, betaine and water is 80-94:23-25:23-25:

500.

5. The method according to claim 1, characterized in that In the step 3), the mass ratio of the adsorbed straw, the volume of the suspension and the mass ratio of the straw to be fermented is 180-190 g:500 mL:3.1-3.3 kg.

6. The method according to claim 1, characterized in that In the step 3), the carbon-nitrogen ratio of the straw to be fermented is 30:1, and the moisture content is 60-62%.

7. The method according to claim 1, characterized in that The conditions for aerobic fermentation in step 3) include: turning the compost twice a day.

8. The method according to claim 1, characterized in that: The granular straw includes rice straw and / or corn straw; The straw to be fermented includes rice straw and / or corn straw.

9. The method according to claim 8, characterized in that The rice straw has a moisture content of 10%, a cellulose content of 40.1%, and a lignin content of 6.3%, all of which are mass percentages.

10. The method according to claim 8, characterized in that The corn stalks have a moisture content of 11%, a cellulose content of 34.7%, and a lignin content of 5.3%, all of which are mass percentages.